Thermally activated ferroelectric domain growth due to random defects - V. Likodimos; Labardi, M.; Orlik, X.K.; Pardi, L.; Allegrini, M.; Emonin, S.; Marti, O. (Physical Review B - Condensed Matter and Materials Physics, 2001)
Ferroelectric domain kinetics on cleaved triglycine sulfate, quenched at different temperatures in the ferroelectric phase, is investigated in situ by scanning force microscopy in the dynamic contact mode. Thermally activated domain growth and dynamic scaling, in accordance with theoretical predictions for quenched disorder due to random-bond defects, is inferred from the temporal evolution of the spatial correlation functions and the related characteristic length scale.
cited By 32